Predicting Iranian road accidents: application of the theory of planned behavior - Seyed Saeed Mazloomy Mahmoodabad; Batool Zeidabadi; Mohammad Reza Rajabalipour (International Archives of Health Sciences, 2023)
Objectives: The aim of this research was to investigate the application of the theory of planned behavior (TPB) in predicting the influential factors in Iranian road accidents.Methods: This cross-sectional, descriptive-analytical study involved a population of 240 Iranian drivers, with a mean age of 39.1 years and a mean driving experience of 16.5 years, selected through a convenient available sampling method. The study utilized questionnaires based on the theory of planned behavior construct and Manchester Driving Behavior. The collected data were analyzed using one-sample t-tests, Pearson correlation, and linear regression in SPSS version 26.Results: The findings indicated that 62% of driving behavior variance could be predicted by the variables of attitude, behavioral intention, and drug abuse. Additionally, drug abuse and drunk driving were significant factors in determining the attitude and behavior of drivers.Conclusion: The theory of planned behavior is a suitable conceptual framework for planning interventions to reduce traffic accidents. This study highlights the most important predictors of drivers' behaviors leading to accidents and identifies the relationships between them to reveal the main priorities. Based on the results, policymakers and stakeholders can plan effective and practical interventions to reduce casualties and promote compliance with accident prevention behaviors.